Scleral fixation of fluocinolone acetonide implant - Homayoun Tabandeh; Kourous Rezaei (American Journal of Ophthalmology Case Reports, 2020)
Purpose: To report on the technique of scleral fixation of fluocinolone acetonide (FAc) implant in 2 eyes with recalcitrant diabetic macular edema (DME). Observations: Two eyes of 2 patients with persistent DME, partially responsive to anti-VEGF therapy, underwent intravitreal FAc implant injection. First case had a history of pars plana vitrectomy (PPV) and scleral fixated posterior chamber intraocular lens implant (PCIOL) for retained lens fragments and dislocated IOL. Subsequently, the patient presented with intermittent anterior chamber migration of the FAc implant associated with an increase in DME. The FAc implant was fixated to the sclera, preventing further migrations, and improving the DME. The second case had a history of persistent DME, PCIOL with open capsule, epiretinal membrane (ERM), and a free-floating FAc implant within the vitreous cavity. She underwent PPV, membrane peel, and simultaneous scleral fixation of the free-floating FAc implant. The surgical technique included 23 G PPV, externalization of FAc implant, re-implantation and scleral fixation through the same sclerotomy utilizing a 10/0 prolene suture. Conclusions and Importance: A surgical technique for scleral fixation of FAc implant is described. The technique is valuable in the management of patients with persistent diabetic macular edema or uveitis who benefit from treatment with fluocinolone acetonide implant but are at risk for anterior chamber migration of the implant.